Implementing Technical Acceptance Model and Its Impact on the Positive Word of Mouth of BCA Mobile Users in Bandar Lampung - Rinaldi Bursan (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
The advancement of information technology, telecommunications, and the internet has resulted in the emergence of various internet-based business applications. Bank Central Asia (BCA) is one such institution that leverages internet technology to serve its customers through its mobile application, MBca Mobile. This research investigates whether the variables of satisfaction and usability influence customer loyalty and subsequently generate positive word of mouth among MBca users. This study aims to determine the effect of satisfaction and usability on loyalty and its impact on positive word of mouth among MBca users. A sample of 150 participants was analyzed using multiple linear regression. The results indicate that satisfaction significantly mediates the relationship between usability and loyalty, which in turn has a substantial positive impact on word of mouth. Consequently, all hypotheses in this study are accepted. It is suggested that BCA enhance the MBca service connection to prevent transaction failures by collaborating with telecommunications providers to ensure reliable internet connections. Additionally, improving operator capabilities through training can increase the speed and accuracy of the service.